Authorization, Contestation and Essentialization: A Multidisciplinary Analysis of Musical Meanings and Religious Discourses in Film and Television - Edholm, Charles (Université d'Ottawa | University of Ottawa, 2026)
This dissertation is a study of relationships between musical meanings and religious discourses in music for film and television. By joining a discursive perspective on the category of religion to a multimodal theory of music in media the study analyzes (1) how music participates in the construction of “religious” meanings in instances of multimedia and (2) how those meanings are necessarily multiple, dynamic, contestable and historically contingent. It does so through a series of audiovisual case studies intended to highlight the socially formative processes of authorization, contestation and essentialization at work in the production of semantic meaning, both musical and religious. Chapters 2 and 3 discuss the musical borrowing of pre-existing hymns as appeals to authority and authenticity in two religious dramas and the genre of horror, respectively. Chapter 4 explores the orientalist construction of a spiritual or mystical East by comparing the distinct religious paradigms and musical treatments of two film adaptations of the Japanese novel Silence. Chapter 5 extends the discussion of cultural and religious contest to the modern notion of the secular as opposite religion, considering a contradictory musical characterization of science, technology and transcendence as religious systems in the genre of science fiction. Chapter 6 concludes with the topic of religious essentialism as expressed by the “world religions” paradigm in documentary film, highlighting the tension between implications for music and religion where the former always carries traces of cultural particularity that the latter intends to transcend. Altogether, each case study demonstrates how fundamental ambiguities regarding the category of religion amplify music’s representative flexibility in an adaptable, mutually reinforcing and self- sustaining semiotic discourse.
Keywords: Film Music; Religion; Religion and Film; Audiovisual; Multimodal; Discourse